Overexpression of LncRNA BM466146 Predicts Better Prognosis of Breast Cancer - Zhang, Yunxiang; Dong, Xiaotong; Wang, Yang; Wang, Liquan; Han, Guiyan; Jin, Lvcheng; Fan, Yanping; Xu, Guodong; Yuan, Dawei; Zheng, Jie; Guo, Xiangyu; Gao, Peng (Frontiers in Oncology, 2021)
This study analyzes the expression and clinical significance of long non-coding RNA (lncRNA) BM466146 in breast cancer, and explores the role of BM466146 in immune regulation. The expression of BM466146 in 89 cases of breast cancer and their corresponding non-cancerous breast tissues was detected by quantitative real-time polymerase chain reaction(qRT-PCR). Kaplan-Meier survival analysis was applied to evaluate patient survival. EDU and CCK-8 experiments on breast cancer cells were performed to verify the function of BM466146 in vitro .The target genes of BM466146 were screened by informatics analysis to predict associated miRNAs and their corresponding mRNAs, immune genes associated with lncRNAs and chemokines associated with CD8. Immunohistochemistry was used to detect the expression of CD8, Ki-67 and CXCL-13 in the 89 breast cancer tissues. It was found that the expression of lncRNA BM466146 in breast cancer tissues was significantly lower than that in normal breast tissues (P < 0.001). In breast cancer, tissues that overexpressed BM466146 exhibited a lower Ki-67 index compared with that of low BM466146 expression (P = 0.048). Kaplan-Meier survival analysis showed that breast cancer patients with overexpression of BM466146 had longer overall survival. EDU and CCK8 experiments showed that overexpression of BM466146 inhibited the proliferation of breast cancer cells. The hsa-miR-224-3p is associated with BM466146, and its target gene might be CXCL-13. The positive CD8 cells in the BM466146 overexpression group was higher than that in the low BM466146 expression group (P=0.027), and the positive CD8 cells in the CXCL-13 positive group was higher (P=0.023) than that of the negative group. Our results indicate that the lncRNA BM466146 has the function of tumor suppressor gene. Overexpression of BM466146 is associated with better prognosis. BM466146 could regulate CXCL-13 by adsorbing hsa-miR-224-3p and inducing CD8+ T cells to accumulate in the tumor area which regulate immune response. Therefore, BM466146 could be a prognostic biomarker and a molecular immune target of breast cancer.